INOVASI PENDIDIKAN DALAM PERSPEKTIF PESANTREN : Studi Tentang Pola Inovasi Sistem Pendidikan di Pondok Pesantren - Minhaji Minhaji (LP2M Universitas Ibrahimy, 2014)
The innovation education in boarding schools, is a part of the efforts to solve the problem when the conventional and traditional way is deemed no longer relevant today. Innovation, substantively, has three characters: concept /theory, technology, new functions and structure. There are three patterns of innovation in boarding school: 1). Innovation initiated by the Government, 2). LP3ES P3M, and 3). The autonomy of boarding school, thus leading to the realization of the ideal boarding school (Pondok Pesantren).